Efficacy of Kraus-Weber Exercise Protocol in the Management of Chronic Mechanical Low Back Pain (2003)
Objective: This study was carried out to determine the efficacy of Kraus-Weber exercises in the management of chronic mechanical low back pain (CMLBP). Design: The equivalent group experimental design was used in the study. Sample Size and Sampling Technique: Thirty volunteer participants with diagnosis of CMLBP took part in the study. The fish bowl technique of simple random sampling was used to assign subjects into either the experimental (Kraus-Weber) or control (non-Kraus-Weber) group. Interventions: Pain intensity, lumbar spine flexibility and functional abilities confidence level (FACL) were assessed before and after 6 weeks of treatment. Subjects in the experimental group were treated using Kraus-Weber exercise, heat therapy, massage and back care education. Subjects in the control group were also treated with heat therapy, massage and back care education excluding Kraus-Weber exercise. Data obtained were analyzed using descriptive statistics and inferential statistics of Student t-test and Spearman rank correlation coefficient (Rho). Significance was set at 0.05 alpha level. Results: Results obtained showed that there was no significant difference in the pre-treatment parameters of the two groups studied. There was significantly greater reduction in the post-6-weeks treatment pain intensity and significantly higher post-treatment functional abilities confidence level of the experimental than the control group subjects. Patient's abilities confidence level was found to increase as their pain intensity decreased. Conclusions: Kraus-Weber exercise is an effective tool in the management of CMLBP when combined with heat therapy, massage and back care education. Kraus-Weber exercise in addition to other modalities was therefore recommended in the management of CMLBP.